2016
DOI: 10.5897/err2016.3014
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of teachers questioning strategies

Abstract: The objectives of this study are;1) to know kinds of teachers' questioning strategies that teacher use in the classroom. 2) to know the way the teachers use the questioning strategies in the classroom. The design of the research is descriptive qualitative. The writer got the data of this research from interview notes. The observation sheet source of the data research were from the teacher and students. The Instrument used are observation sheet, interview, and document. The techniques for analyzing the data is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 10 publications
(9 reference statements)
1
9
0
2
Order By: Relevance
“…In this regard, in total over the six sessions, the convergent questions were found to be the most frequent type of questions used by the instructor with 148 questions (52%), followed with 78 divergent questions (27%), 58 procedural questions (20%), and 2 rhetorical questions (1%) consecutively. This study in line with a study conducted by Dos, Bay, Aslansoy, Tiryaki, Cetin, and Duman (2016) who found that the two most frequently used questions comprised convergent and divergent questions.…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, in total over the six sessions, the convergent questions were found to be the most frequent type of questions used by the instructor with 148 questions (52%), followed with 78 divergent questions (27%), 58 procedural questions (20%), and 2 rhetorical questions (1%) consecutively. This study in line with a study conducted by Dos, Bay, Aslansoy, Tiryaki, Cetin, and Duman (2016) who found that the two most frequently used questions comprised convergent and divergent questions.…”
Section: Discussionsupporting
confidence: 91%
“…(2016) suggested that the questioning strategy helps students develop their interest in the lesson content by promoting students’ rational thoughts, allowing teachers to eliminate their confusing thoughts, highlighting important ideas and concepts, evaluating their understanding, and encouraging their participation in the lesson. Therefore, questions and questioning skills are essential for language teachers to motivate students not only to provide appropriate responses but to ask questions themselves ( Bulent et al., 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although all these mentioned indicate correct uses, teachers further stated that they use divergent questions to determine whether students comprehend certain concepts, to activate their prior knowledge and to ensure that students express themselves. However, using convergent questions for the previously-mentioned purposes is easier and more reasonable (Bulent et al, 2016;Çakır & Cengiz, 2016). Therefore, based on the results of the study, the type of Batam elementary school teacher questions needs to be improved.…”
Section: Implementedmentioning
confidence: 99%
“…Moreover, the study explained that teachers are expected to ask higher-level questions for higher-level learning. In addition to improving students" critical thinking skills, high-level questioning stimulates students" active participation and facilitates learning (Bulent et al, 2016;Nalole, 2010). Student responses to the questions given by the teacher during learning were also studied in this study.…”
Section: Implementedmentioning
confidence: 99%
See 1 more Smart Citation